Legal Guerilla: Jurisdiction, Time, and Abortion Access in Mexico City - Amy Krauss (Revista Direito GV)
Abstract This article traces the emergence of a new politics of jurisdiction in legal abortion debates in Mexico. It analyzes how jurisdictional claims work as a kind of lawfare from “above” and “below” examining: 1) how the Mexican Supreme Court invoked technicalities of jurisdiction to settle the constitutional conflict over the decriminalization of abortion in Mexico City, and 2) how a feminist litigator reappropriated the court's formal principles of legality toward their own ends in what they call “legal guerilla.” Drawing on ethnographic fieldwork in Mexico City, the author explores how competing jurisdictions create ambiguous spaces and temporalities of inclusion and exclusion from legality and clinical care. In closing, she argues that feminist activists who work to create access and people who seek abortion enact their own forms of “legal guerilla” as they move through these overlapping and contradictory legalities.